Результаты клинической апробации модели системы кровообращения в виде согласованной длинной линии - Владов, С. И.; Аврунин, О. Г.; Мосьпан, В. А.; Юрко, А. А. (НТУ "ХПИ", 2014)
В работе представлены результаты тестирования процесса движения крови по сосудам в клинических условиях, которые свидетельствуют о высокой объективности показателей модели системы кровообращения человека в виде неоднородной согласованной длинной линии с распределенными параметрами для определения гемодинамических показателей при диагностировании функциональных нарушений системы кровообращения человека. По результатам клиническая апробация доказано, что данная модель может использоваться для определения объективных показателей движения крови по сосудам при функциональных нарушениях системы кровообращения человека за критериями доказательной медицины.

The results of the testing process, the movement of blood through the vessels in the clinical setting, which indicates the high objectivity performance mathematical model of the circulatory system in the form of a long line with the up-diffused parameters to determine the hemodynamic parameters in the diagnosis of functional disorders of the circulatory system of man. During the course of the clinical trials were investigated following a pathological condition of the patients: aortic hypertension, aortic stenosis, ischemic stroke in the internal carotid arteries and coronary heart disease. According to the results of clinical testing proved that the model can be used to determine objective measures of blood flow through the vessels in functional disorders of the circulatory system of the human criteria of evidence-based medicine. Based on this model can be developed new diagnostic methods. General exactness of the model, which makes it possible to argue about the adequacy of the model of the human blood circulation system as a method of diagnosis of several diseases of the human blood circulation system was also set.
Results of clinical trials of model of the human blood circulation system in the form of a concerted-noah to long line
Keywords: результаты тестирования; процесс движения крови; сосуды; model; long line; blood circulation system